The Role of Innovative Leadership in Building Organizational Commitment To ESG: A Case Study of Environmental Startups in Indonesia - Danang Pratomo; Achmad Husen; Dian Alfia Purwandari; Yeni Astuti; Akhmad Qosasih (Jurnal Indonesia Sosial Teknologi, 2025)
Green bonds are becoming an increasingly popular financial instrument to finance sustainable environmental projects. However, there are still significant challenges related to transparency, accountability, and accurate impact measurement. This research aims to design an integration model of ESG (Environmental, Social, and Governance) indicators in a blockchain-based system to increase transparency and investor trust. The research method uses the Research and Development (R&D) approach with the Borg & Gall model, through the stages of literature study, model design, expert validation, and system flow simulation. The results show that blockchain can be used as a reliable framework for smart contract-based ESG reporting and distributed ledger. This model demonstrates the potential in improving project accountability and attracting more institutional investors to green finance instruments. The research offers significant practical value by equipping financial institutions with a tool to mitigate greenwashing risks and enable real-time monitoring of ESG compliance. For policymakers, it presents a scalable framework to standardize reporting requirements, particularly in emerging markets where green finance is rapidly growing. Theoretically, the research contributes to the discourse on blockchain applications in sustainable finance by demonstrating its potential to resolve principal-agent problems in impact investing. Additionally, the integration of smart contracts with ESG metrics opens new avenues for automating sustainable financial instruments, paving the way for future technological innovations in this domain.